Espécies não nativas e a biodiversidade: um estudo de caso sobre camarões peneídeos no estuário do rio Acaraú, Nordeste do Brasil - Silva, Grasielle Dayse de Vasconcelos (2023)
Shrimp farming is an important aquaculture activity in the brazilian northeast region, with enterprises generally located close to estuaries, and the main cultivated species is the gray shrimp from the Pacific Penaeus vannamei (BOONE, 1931). Although the productive success of aquaculture pulses, the problem with the escape of exotic species is imminent. Biological invasions put pressure on native fauna and natural habitats. Thus, the hypothesis of this work was that P. vannamei is present in the estuary of the Acaraú river, Ceará, Brazil and has established populations. The overall objective was to characterize the shrimp assemblage in the Acaraú river estuary and to investigate invasive penaeid shrimp. Therefore, shrimp collections were carried out along the Acaraú River estuary, for 12 months, and abiotic parameters of water and soil were measured. After determining the ecological indices and statistical tests, the results found were: 593 shrimp, the native species P. brasiliensis, P. schmitti and P. subtilis, as well as the non-native species P. vannamei, with P. subtilis being the most abundant and dominant; the months March/2022, April/2022 and May/2022 had the highest catches, so that in March 356 individuals were found, April had 116 individuals and 97 individuals in May. Transparency and pH together statistically had more influence on the structure of the shrimp community in the study site. The largest species were mainly P. vannamei. Although without established populations, they were recurrent in the studied natural environment, P. vannamei can become bioinvasive and continuous monitoring will be necessary in the estuary of the Acaraú River. Monitoring of this species was suggested, in addition to the need for greater rigidity in legislation and future genetic studies that reveal the real origin of the species in the estuary and environmental education programs.